On the Organochlorine pesticide residues in the Marshes, Shatt Al-Arab and the Arabian Gulf system - Douabul , A.A.Z.; Al-Timari, A.A.K. (Mesopotamian Journal of Marine Sciences, 2022)
Organochlorine pesticides are a class of toxic compounds characterized by their relative chemical and biological stability. They are ubiquitous in the environments and are soluble in liquids. Consequently Organochlorine pesticides have been placed on “the top of black list” of potential environmental hazards. Studies on Organochlorine residues have been carried out between 1979-1991. The residues were determined in water, sediments and organisms collected from the Marshes, Shatt Al-Arab and the Arabian Gulf system. Most of the data confirmed the present of ∑DDT, Endrin, Dieldrin, Chlordane and Heptachlor. Their concentrations ranged from nd-336, nd-111, 12-195, nd-57 and nd-79 ng/l in dissolved, from 0.1-2560, nd-217, nd-0.97 , nd-171 and nd-679 µg/kg in particulate and from 0.04-220, nd-47, nd-22, nd from nd-24 µg/kg in sediments from 1-189, nd-154, nd-32, nd-58 and nd-6 ppb in fish, from 0.59-784, 166-540, 2-72, 5-3.1 and nd ppb in mussel and from 0.3-6.3, nd-0.4, nd-0.8, nd and nd-0.3 ppb in shrimp respectively. In the last decade only two studies on Organochlorine residues have been done. One of them in the Mesopotamian wetlands of southern Iraq in which residues of p,p´-DDT have been detected in 100% of the examined samples. This indicates its ability to persist under severe drying of previously exposed surface sediments, long period of more than 10 years of previously exposed surface sediments, high temperature, and intensive solar radiation, and the other by using samples of water, sediment, fish and shrimp from Hor Al-Hammar Marshes of Iraq, high concentration of chlordane in both water and sediments were shown. Therefore further work is needed to establish the baseline levels of Organochlorine residue in the Marshes, Shatt Al-Arab and the Arabian Gulf region.